Analysis of Factor Influencing Timelines of Financial Reporting (Empirical Studi on Banking Companies Listed on the IDX in 2018-2021) - Amirawati (JEKAMI Journal of Accounting, 2023)
The purpose of this study the factors that affect the timeliness of financial reporting in banking companies in 2018-2021 lised on the IDX. The factors tested in this study were profitability, audit committee, and firm size. The tipe of data used is secondary data obtained form www.idx.co.id. The sampel of this study used 20 companies and was selected by purposive sampling. The analytical method used in this sudy is panel data regression analisis with the Eviews 9 program. The results of this study indicate that the variables of profitability and audit committee have no significant effect on the timeliness of financial reporting. While the size of the company has a significant effect timeliness of financial reporting..